EFFECT OF SELECTED PLANT EXTRACTS AND CHEMICALS EFFECT OF SELECTED PLANT EXTRACTS AND CHEMICALS AGAINST SOUR ROT ( AINST SOUR ROT (Geotrichum candidum) OF TOMATO (Lycopersicon esclentum). ycopersicon esclentum). ycopersicon esclentum). - M. ABDULRAHMAN, ABDUALALEIM; RAKHI MURMU; SOBITA SIMON; ABHILASHA A. LAL (The Bioscan, 2018)
Sour rot caused by Geotrichum candidum is one of the most important disease affecting tomato. CaCl2 (5.73 cm) and papaya (6.68 cm) significantly inhibited the radial mycelial growth of the pathogen as compared to control (9.05 cm), physiological loss in weight was minimum in acetic acid (36.61%) and eucalyptus extract (39.01%) as compared to control (58.23% ). Higher lycopene content of tomato was obtained in CaCl2 (4.57mg/100g) followed by aleovera (4.54mg/100g), papaya (4.51mg/100g) as compared to control (4.57 mg/100g). Higher ascorbic acid content of tomato was obtained from CaCl2 (20.1mg /100g), papaya leaf extract (19.8mg/100g) as compared to control (16.2 mg/100g). Total soluble solids (ºBrix) of tomato was highest in CaCl2 (5.2%) followed by papaya (4.42%) as compared to control (4.1%). Calcium chloride and papaya leaf extract treated fruits showed significant levels of delay in weight loss, firmness, total soluble solids, vitamin C and lycopene content, so they can be used as a potent natural antifungal agent.